The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3851/imp3197
|View full text |Cite
|
Sign up to set email alerts
|

Viro-Immunological Response of Drug-Naive HIV-1-Infected Patients Starting a First-Line Regimen with Viraemia >500,000 Copies/ml in Clinical Practice

Abstract: In this multicentre retrospective study, patients with viraemia >500,000 copies/ml who start a first-line regimen containing PI+INI or NNRTI yield a better VS compared to those receiving a PI-based regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These results suggested that for patients with very high baseline HIV-RNA levels, more potent initial regimens are needed. A recent study in treatment-naïve patients with similar HIV-RNA levels demonstrated that the overall probability of viral success by 48 weeks was 80.1% on intensified regimen of 2NRTIs+PI+ INSTI, higher than other groups receiving 2NRTIs+NNRTI or 2NNRIs+PI [23]. Therefore, more potent initial treatment such as four-drug combination for patients with very high baseline HIV-RNA levels, for the purpose of achieving virologic suppression as soon as possible, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that for patients with very high baseline HIV-RNA levels, more potent initial regimens are needed. A recent study in treatment-naïve patients with similar HIV-RNA levels demonstrated that the overall probability of viral success by 48 weeks was 80.1% on intensified regimen of 2NRTIs+PI+ INSTI, higher than other groups receiving 2NRTIs+NNRTI or 2NNRIs+PI [23]. Therefore, more potent initial treatment such as four-drug combination for patients with very high baseline HIV-RNA levels, for the purpose of achieving virologic suppression as soon as possible, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by the fact that only patients with treatments including two NRTIs plus one PI or one INI or efavirenz were included in this French study. Indeed, selection might underestimate the number of patients with very high pre-cART viral load that might receive alternative treatments [10]. For this reason, in our analysis, we decided to include all patients treated with at least three drugs among at least two antiretroviral classes (regardless the recommended first-line regimens) to better represent real settings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with documented acute infection were excluded. Analyses were performed by stratifying patients in the following pre-cART strata [9][10][11]18]: 100,000, 100,001-500,000, 500,001-1,000,000, and >1,000,000 copies/mL. Reference viremia levels (dummies) were <100,000 and 500,000-1,000,000 copies/mL in order to evaluate the risks of VR in patients with pre-cART viremia ranging 100,000-500,000 and >1,000,000 copies/mL.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations